Effects of a greater incentive to attack the head and face region on incidence of head kicks and concussions among male youth taekwondo competitors - Koh, J. O. (The Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROUND: In an attempt to improve the technical quality of sparring taekwondo, the World Taekwondo Federation has amended the competition rule for a head kick (HK), increasing the number of points awarded for this type of attack. The purpose of the current study was to: 1) evaluate the incidence of HKs and concussions; and 2) identify potential risk factors of concussions in sparring taekwondo. METHODS: A postmatch, interview-based prospective cohort study was conducted with 145 sparring taekwondo athletes (12-16 years of age) who: 1) competed at a 2018 sparring-Taekwondo tournament; and 2) received a valid HK during competition. Incidence rates of HKs and concussions were estimated; possible risk factors or prognosticators of concussions were also analyzed using the chi-square test and binary logistic analysis. RESULTS: Incidence rates of HKs and concussions were 133.5 (95% CI: 113.3-153.8) and 41.4 (95% CI: 29.6-53.3) per 1000 athlete-exposures, respectively. The binary logistic model revealed that athletes with no prior concussion history were less likely to experience a concussion (OR, 0.27; 95% CI: 0.1-0.7). CONCLUSIONS: Although the incidence rates of HKs and concussions are considerably high, they are not increased compared with the results of pre-2009 studies. Therefore, the new competition rule relating to HKs did not appear to increase the incidence rates of HKs or concussions in our research participants. To prevent adverse effects related to repetitive HKs and concussions, continuous research is needed.